Tahlil Marriage Among the Sasak Tribe of Lombok Based on Maqashid Al-Shari’ah Perspective and Its Relevance to Compilation of Islamic Law - Arifin H. Munir, Zainal; Nurul Wathoni, Lalu Muhammad; Bin Mujib, Lalu Supriadi; Dahri, Harapandi (al-'adalah, 2022)
This study examines the practice of Tahlil Marriage carried out in several sub-districts in East Lombok Regency. Tahlil marriage or Cine Bute or muhallil is carried out as a condition that reconciliation between ex-husband and ex-wife who has been divorced is permissible. Tahlil Marriage (Cine Bute) in the Sasak community is carried out secretly without authorization from the Office of Religious Affairs. This research is classified as qualitative research with an empirical normative approach. Data were collected using observation, interview and documentation techniques and were analyzed through the perspective of Maqasid al-Shari’ah and Compilation of Islamic Law (KHI). This research found that Tahlil marriage in East Lombok Regency was divided into three forms: common marriages, contractual marriages, and common marriages initiated by contract marriages. In the view of Maqasid al-Shari'ah, the Tahlil marriages carried out by the Sasak tribe do not fulfill the aspects of dharuriyya, hajjiyat and tahsiniyyat. Among the factors that influence the Tahlil marriages performed by the Sasak tribe are the ease of divorce, the lack of public legal awareness, the low level of public education, the lack of understanding of religion and the weakness of law enforcement.